Aplicación de la simulación Monte Carlo en la administración de proyectos utilizando Excel y @Crystal Ball (ING) - Azofeifa, Carlos (2002)
Simulation Monte Carlo is an effective technique used to analyze the critical path in a project, this simulation will be used to estimate the probability of finishing the project on time. Monte Carlo is necessary due to the hight uncertainty showed in the estimations of time operations from the differents activities in the project. For facility the calculations, @Crystal Ball software is a popular spreadsheet add-in used for simulations and risk analysis.